Sliding friction unit of connecting-rod end of high-lift plunger pump using self-lubricated bearing from powder antifriction material - Marina V. Korchagina; Sergey O. Kireev; Sergey L. Nikishenko; Alexey D. Kuzin (Advanced Engineering Research, 2017)
Introduction. The powder antifriction materials applied in the oil and gas industry are considered. Special attention is given to the materials with the effect of self-lubricity. The use of such materials in a frictional unit of one of the most widespread types of the oil and gas well service equipment - a high-lift plunger pump - is offered. The pump construction diagram with the description of the modernized unit is provided; the problems arising under the production and exploitation of the connecting-rod pin bearing group are described. Materials and Methods. Upon the experience in applying bearing bushes from powder antifriction materials in mechanical engineering, the iron graphite porous material is selected. The design change considering the self-lubricating materials behavior and allowing the best usage of their properties is made. The bushing-to-shaft gap, one of the most important parameters of the plain bearer performance, is considered. The fit providing the fullest seating of the bushing to the shaft is selected. That improves the heat removal, promotes the even load distribution over the frictional area, and so enhances the operating capacity of the bearing unit. Research Results. A change option of the frictional unit design of a connecting-rod small power end with the use of the self-lubricated bearing from the powder antifriction iron-based material is offered. The proposed bearing meets the loading conditions of the considered unit. The design is developed due to the condition of self-lubricity that allows simplifying the production of a connecting rod obviating the manufacturing of oilholes in the connecting rod body. The analysis of the offered modernization is carried out with the application of 3D modeling. The constructed models permit to visually estimate the simplification of the entire connecting rod design, the production of its constituent parts, as well as its assembling. Discussion and Conclusions . The obtained models allow drawing a conclusion on the feasibility of the bearing design change for the sliding friction unit of the connecting-rod end of the high-lift plunger pump using the powder antifriction material to replace the existing one. The application of this bearing with the effect of self-lubricity will allow a substantial simplification of the pin bearing unit design.